Writing with a thesis : - Skwire, David (Harcourt Brace College, 1998)
The book is truly basic: spelling, grammar, sentence structure, and punctuation. It stresses writing; thinking. It uses little linguistic terminology; and has abundant practice sentences and paragraphs. It includes groups of thematically related, informative sentences on such subjects as a field of diamonds in United states, pigeon racing, famous people... The book also provides answers at the back of it. And at the end, it includes five essays to read and summarize